2007
DOI: 10.1098/rspb.2007.1073
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for adaptive design in human gaze preference

Abstract: Many studies have investigated the physical cues that influence face preferences. By contrast, relatively few studies have investigated the effects of facial cues to the direction and valence of others' social interest (i.e. gaze direction and facial expressions) on face preferences. Here we found that participants demonstrated stronger preferences for direct gaze when judging the attractiveness of happy faces than that of disgusted faces, and that this effect of expression on the strength of attraction to dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 19 publications
6
58
0
1
Order By: Relevance
“…In a similar vein, studies have shown that participants generally prefer faces with direct gaze to those with averted gaze (Mason et al 2005;Conway et al 2008a), but that these preferences are stronger when judging oppositesex than own-sex faces (Mason et al 2005;Conway et al 2008a), physically attractive faces than physically unattractive faces (Conway et al 2008b), and faces with happy expressions than faces with disgusted expressions (Conway et al 2008a). Integrating information about the sex and physical attractiveness of others with information about the direction and valence of their social interest in this way may serve an important function during social interactions by promoting efficient and effective allocation of social effort (ie by promoting allocation of more social effort to the most attractive individuals who appear willing to reciprocate öConway Jones et al 2006;Mason et al 2005;O'Doherty et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, studies have shown that participants generally prefer faces with direct gaze to those with averted gaze (Mason et al 2005;Conway et al 2008a), but that these preferences are stronger when judging oppositesex than own-sex faces (Mason et al 2005;Conway et al 2008a), physically attractive faces than physically unattractive faces (Conway et al 2008b), and faces with happy expressions than faces with disgusted expressions (Conway et al 2008a). Integrating information about the sex and physical attractiveness of others with information about the direction and valence of their social interest in this way may serve an important function during social interactions by promoting efficient and effective allocation of social effort (ie by promoting allocation of more social effort to the most attractive individuals who appear willing to reciprocate öConway Jones et al 2006;Mason et al 2005;O'Doherty et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast with this emphasis on the effects that physical cues have on facial attractiveness, recent studies have also investigated the ways in which the effects of these invariant physical cues and those of changeable social signals, such as gaze direction and expression, might interact when judging the attractiveness of others (eg Conway et al 2008a;Jones et al 2006;Kampe et al 2001;O'Doherty et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies, however, have demonstrated that facial attractiveness is influenced by interactions between relatively invariant physical cues in faces and more changeable social signals, such as gaze direction (Conway et al 2008a(Conway et al , 2008bJones et al 2006;Kampe et al 2001). For example, Jones et al (2006) found that preferences for attractive colour and texture cues were stronger when judging the attractiveness of faces that were smiling at the viewer than when judging faces that were looking at the viewer with a neutral expression or that were looking away from the viewer.…”
Section: Introductionmentioning
confidence: 99%
“…Technical details of the averaging procedure we used to manufacture these prototypes are given in Tiddeman et al (2001). These methods have been used to generate face stimuli in many previous studies (eg Conway et al 2008aConway et al , 2008bConway et al , 2009DeBruine et al 2006;Jones et al 2004Jones et al , 2005Jones et al , 2006Perrett et al 2002).…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation